Management of orthopaedic infections a practical guide - Chen, Antonia (Thieme, 2021)
"Orthopaedic infections represent common, potentially devastating, and sometimes fatal complications that can occur after any surgery. Infections associated with orthopaedic trauma are especially prevalent, and there is an increasing incidence of bone infections linked to a greater number of joint arthroplasties being performed annually. Management of Orthopaedic Infections: A Practical Guide by renowned orthopaedic surgeon and researcher Antonia Chen is a practical clinical reference to assist clinicians in the diagnosis and treatment of challenging infections spanning the entire orthopaedic specialty"--